PL.82 An Audit of Compliance with Current Guidelines on the Management of Third and Fourth Degree Tears in the Rotunda Hospital. (26th April 2013) - Doyle, A; Cooley, S; Halloran, K O'; Whelan, M; Eogan, M
Abstract : 3 rd and 4 th degree tears occur in 1% of vaginal deliveries. In the Rotunda the rate in the first six months of 2012 was increased at 3%. The aim of this audit was to assess compliance with current Rotunda guidelines and where non-compliance was identified assess if complications arose as a result. A retrospective chart review of all third and fourth degree tears was performed. There were 51 cases during this time period and 47 charts were available for review. The comparison standard was the Rotunda Hospitals "Guidelines for Management of Episiotomy and Repair of Perineal Trauma" Sept 2010. There were 51 cases in total. 45% were following Spontaneous vertex delivery, 27% following ventouse delivery, 14% following combination of ventouse and forceps and 14% forceps alone. 100% were repaired under regional anaesthesia. Only 66% received the correct dose and duration of antibiotics. 95% received laxatives post delivery with only 51% received appropriate non-opiate analgesia. 44.6% of patients were reviewed by senior staff and 81% received physiotherapy. 87% were followed up in the perineal clinic. Review of current perineal repair form should be performed to include headings more specific to third/fourth degree tears. A sticker highlighting that the patient has had a third/fourth degree tear should be placed on the front of drug Kardex. This may help avoid prescription of opiate analgesia. All women receive an information leaflet on discharge. Women should have senior staff review day 1 postpartum. It should be re-audited in six months.